1999
DOI: 10.1097/00007890-199901270-00024
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Graft Size Mismatching on Graft Prognosis in Liver Transplantation From Living Donors1,2

Abstract: The use of small-for-size grafts (less than 1% of recipient body weight) leads to lower graft survival, probably through enhanced parenchymal cell injury and reduced metabolic and synthetic capacity. Although large-for-size grafts are associated with some anatomical and immunological disadvantages, the negative impact is less pronounced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
755
3
15

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 897 publications
(792 citation statements)
references
References 26 publications
14
755
3
15
Order By: Relevance
“…Graft mass is a critical variable affecting outcomes and a limitation in the extension of SLT between two adults. Adequate graft mass has been extensively explored in living donor liver transplantation with minimal graft thresholds advocated (48)(49)(50)(51)(52); however, these data are not directly applicable to SLT as parenchyma quality, and immediate function of living donor grafts exceeds that of cadavers (27,53,54). Our preference is a graft mass of at least 1% recipient body weight; however, grafts less than 0.8% recipient body weight have been utilized with success (30,55,56).…”
Section: Technical Considerationsmentioning
confidence: 99%
“…Graft mass is a critical variable affecting outcomes and a limitation in the extension of SLT between two adults. Adequate graft mass has been extensively explored in living donor liver transplantation with minimal graft thresholds advocated (48)(49)(50)(51)(52); however, these data are not directly applicable to SLT as parenchyma quality, and immediate function of living donor grafts exceeds that of cadavers (27,53,54). Our preference is a graft mass of at least 1% recipient body weight; however, grafts less than 0.8% recipient body weight have been utilized with success (30,55,56).…”
Section: Technical Considerationsmentioning
confidence: 99%
“…However, with reduction of graft size, chances of primary graft nonfunction and complications also increase (1,2). Our previous study revealed that complications might be related to microcirculatory injuries that arose from transient portal hypertension (3).…”
Section: Introductionmentioning
confidence: 99%
“…The graft size is one of the most important factors for recipient survival. Kiuchi et al 5 reported that a GRWR < 0.8% may lead to poor graft survival. Seven of the 13 recipients in this study received an RPS graft with a low weight (GRWR < 0.8%); however, none of the recipients had small-for-size graft dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that adequate donor liver volumetry is one of the key factors for both the safety of living donors and the survival of recipients of adult-to-adult LDLT. 4,5 In addition to an adequate liver volume, the selection of the appropriate liver graft from the donor might be critical for successful adult-to-adult LDLT.In adult-to-adult LDLT, the size of the left lobe (LL) graft is frequently insufficient to meet the metabolic demands of the recipient, whereas the size of the right lobe (RL) graft usually satisfies the liver volume requirements of the recipient. However, RL donation carries a higher risk to the donor than LL donation.…”
mentioning
confidence: 99%
See 1 more Smart Citation